Anoman Angrĕrĕpi Munggeng Nagasĕkar: dari Rubrikasi Hingga Hubungan Intertekstual Sĕrat Rama Jayakusuman dengan Sĕrat Rama Yasadipuran - Sadewa, Tio Cahya (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2023)
This research discusses the rubrication of